Targeting vulnerability with electronic location monitoring: paternalistic surveillance and the distortion of risk as a mode of carceral expansion - Shore, Krystle (Critical criminology, 2021)
Surveillance practices, both state and non-state in origin, are deployed increasingly to solve social problems beyond the traditional domains of criminal justice and national security, including public health concerns. Although such "protective" forms of surveillance are proffered by the state as beneficial for those under surveillance, they nonetheless retain coercive dimensions in practice and require the labeling of a group as "risky" in order to justify their use. Following Shelley Bielefeld’s (2018) observations about protective state surveillance as a form of paternalism, and Jennifer Musto’s (2016) notion of "carceral protectionism," this article uses a case study of the electronic monitoring of people with cognitive impairments to identify the carceral features of paternalistic surveillance and to explore how this practice is justified. I make the argument that, specifically through targeted vulnerability and distortions of risk, paternalistic surveillance practices can operate as a mode of carceral expansion.